Deficit of Cross‐Frequency Integration in Mild Cognitive Impairment and Alzheimer's Disease: A Multilayer Network Approach. Issue 5 (26th November 2020) - Wang, Xiaoyue; Cui, Xiaohong; Ding, Congli; Li, Dandan; Cheng, Chen; Wang, Bin; Xiang, Jie
Abstract : Background: Studies at specific frequencies have shown abnormalities in brain functional networks among mild cognitive impairment (MCI) and Alzheimer's disease (AD) patients. Previous studies have failed to take into account the possibility that optimal cognitive integration requires interactions between different frequency bands. Purpose: To study whether there is abnormal cross‐frequency integration in patients' brains during disease progression. Study Type: Retrospective. Population: Forty‐six normal control (NC), 85 patients with MCI, and 31 patients with AD. Field Strength/Sequence: 3T. Assessment: Multilayer network models were constructed for NC, MCI, and AD, and multilayer participation coefficient (MPC) was used to study the changes of the interlayer relationship in the course of disease development. In addition, MPC and an overlapping degree were combined to classify nodes in the network, and the role of key nodes in the interlayer interaction was mainly observed. Finally, the correlation between multilayer network measures and cognitive function was investigated. Statistical Tests: Pearson chi‐squared two‐tailed test, one‐way analysis of variance (ANOVA), nonparametric Spearman correlation coefficient r, and the false discovery rate. Results: The MPC of the network decreased significantly in MCI ( P < 0.05) and AD ( P < 0.05). The number of intralayer nodes increased significantly (MCI [ P < 0.05], AD [ P < 0.05]) and the number of interlayer nodes decreased significantly. Centrality loss between frequencies of a large number of hub nodes, among which the damaged hub nodes included the left hippocampus, left precuneus, right precuneus, left posterior cingulate gyrus, left precentral gyrus, right precentral gyrus, left medial superior frontal gyrus, and right postcentral gyrus. MPC was significantly associated with memory impairment in patients (AD [Spearman's r = 0.526, P < 0.05], MCI [Spearman's r = 0.229, P < 0.05]), and these related regions included damaged hub nodes in patients. Data Conclusion: In the multilayer networks of patients, there was an obvious deficit in cross‐frequency integration and the hub nodes were preferentially damaged. Moreover, these vulnerable hubs are associated with patients' cognitive scores. Level of Evidence: 1 Technical Efficacy Stage: 3